2021
DOI: 10.1098/rsos.201835
|View full text |Cite
|
Sign up to set email alerts
|

Relative abundance of nitrogen cycling microbes in coral holobionts reflects environmental nitrate availability

Abstract: Recent research suggests that nitrogen (N) cycling microbes are important for coral holobiont functioning. In particular, coral holobionts may acquire bioavailable N via prokaryotic dinitrogen (N 2 ) fixation or remove excess N via denitrification activity. However, our understanding of environmental drivers on these processes in hospite remains limited. Employing the strong seasonality of the central Red Sea, this study assessed the effects of environmental para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Microbial community compositions in coral holobionts are highly selective due to different host functional or life history traits pertaining to e.g., development, physiology, and metabolism ( 17 , 40 , 68 ). Due to a relatively low capacity to obtain (in)organic N sources from the surrounding environment, P. flava is likely to rely more on symbiotic N cycling microbes to acquire or remove N to fulfill its metabolic requirements ( 13 , 28 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial community compositions in coral holobionts are highly selective due to different host functional or life history traits pertaining to e.g., development, physiology, and metabolism ( 17 , 40 , 68 ). Due to a relatively low capacity to obtain (in)organic N sources from the surrounding environment, P. flava is likely to rely more on symbiotic N cycling microbes to acquire or remove N to fulfill its metabolic requirements ( 13 , 28 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, denitrifiers, that is, prokaryotes that encompass the reduction of nitrate or nitrite to dinitrogen gas ( 27 ), might help alleviate excess N stress of holobionts ( 7 ). Denitrifiers appear to be widely associated with many reef organisms and their activity was recently confirmed in corals from the Red Sea ( 28 ). Specifically, it has been observed that the activity of microbial denitrification in coral holobionts increased with environmental N levels ( 29 ).…”
Section: Introductionmentioning
confidence: 95%
“…The significance of the holobiont model for understanding coral nitrogen demand lies in the emerging, yet poorly understood, relationship between the community of microorganisms contributing to the holobiont and how nitrogen is cycled and regulated within corals (Glaze et al, 2022;Mohamed et al, 2022). Recent studies indicate that the holobiont microbial community may be key to regulating fluctuations in environmental nitrogen availability and in maintaining the critical relationship between the coral host and its endosymbionts (Tilstra et al, 2021). More precisely, the holobiont makeup may be important for stabilizing nitrogen availability and maintaining nitrogen limitation in the endosymbiont via the relative actions of denitrifying and nitrogen-fixing bacteria.…”
Section: Nitrogen Cycling In Coralsmentioning
confidence: 99%
“…More precisely, the holobiont makeup may be important for stabilizing nitrogen availability and maintaining nitrogen limitation in the endosymbiont via the relative actions of denitrifying and nitrogen-fixing bacteria. Whilst nitrogen fixation has been reported as a critical process supporting primary production by zooxanthellae endosymbionts during periods of low nutrient availability (Rädecker et al, 2015), it has also been reported that regulation of nitrate availability by microbial denitrification rates can occur when ambient nitrate concentrations are high thus potentially limiting the zooxanthellae response to elevated nutrient levels (Tilstra et al, 2021). Yet despite nitrogen fixation by free-living and colonial pelagic diazotrophs (Bell, 1992;El-Khaled et al, 2020), by benthic organisms (Cardini et al, 2014) and by bacterial symbionts (Lesser et al, 2007) being common within reef environments, nitrogen fixation is currently considered to be only a minor to moderate source of fixed nitrogen in the overall coral nitrogen budget, with estimates generally indicating a supply of <10%, but perhaps reaching as high as 20% under certain specific conditions (Rädecker et al, 2015;Benavides et al, 2017;Glaze et al, 2022;Moynihan et al, 2022).…”
Section: Nitrogen Cycling In Coralsmentioning
confidence: 99%